Zerumbone Sensitizes the Anti-Cancer Efficacy of Cisplatin in Hepatocellular Carcinoma Cells - Jegannathan, Srimathi D.; Arul, Santhosh; Dayalan, Haripriya (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: Zerumbone (ZER) exerts potent antiproliferative, apoptotic, and antiangiogenic functions against variety of cancer cells. Cisplatin (CIS), a standard chemotherapeutic drug, is effective against different types of cancers. However, the combined effect of ZER and CIS on hepatocellular carcinoma remains unknown. Objective: The present study is attempted to examine the effectiveness of the combination of ZER and CIS in liver cancer in vitro using the hepatocellular carcinoma Huh-7 cell line. Methods: Effect of ZER, CIS, and their combination therapy on cell viability and cytotoxicity was assessed by MTT and LDH leakage assays. Cell cycle and apoptosis analysis were performed by flow cytometry. Quantitative real-time PCR was used to examine the m-RNA expression of genes involved in apoptosis, angiogenesis, and invasion. Caspase activity was studied using commercial kit method in the Huh-7 cell line. Results: Cells exposed to ZER, CIS individually, and both together significantly inhibited cell proliferation with IC50 values of 10 μM for ZER and 3 μM for CIS. The combination treatment of ZER and CIS revealed a synergistic effect with a CI value < 1. CIS treatment, either alone or in combination with ZER, caused cell cycle arrest in the S phase. More importantly, ZER combined with CIS exhibited synergistic effects in up-regulating Bax/Bcl-2 ratio, leading to caspase cascade activation. Conclusion: In conclusion, the current study indicates that the treatment of 4.62 μM of ZER combined with 1.93 μM of CIS in human liver cancer cells exerts synergistic effects on cell growth inhibition, apoptosis induction, angiogenesis, and invasion by modulating gene expression.
Keywords: liver cancer